2010
DOI: 10.1186/1471-2458-10-503
|View full text |Cite
|
Sign up to set email alerts
|

Family structure, parent-child conversation time and substance use among Chinese adolescents

Abstract: BackgroundThe family plays a vital role in shaping adolescent behaviours. The present study investigated the associations between family structure and substance use among Hong Kong Chinese adolescents.MethodsA total of 32,961 Form 1 to 5 (grade 7-12 in the US) Hong Kong students participated in the Youth Smoking Survey in 2003-4. An anonymous questionnaire was used to obtain information about family structure, daily duration of parent-child conversation, smoking, alcohol drinking and drug use. Logistic regress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
26
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 40 publications
11
26
1
1
Order By: Relevance
“…The results of their systematic review found that parental monitoring, parent-child interaction, and child disclosure led to delayed alcohol initiation as well as reduced levels of later drinking [68]. Additional support for the findings of the current systematic review were found in the results of other studies which show that parental monitoring significantly decreases adolescent risk behaviour such as sexual risk behaviours and decreased substance use [26,56,60,67]. Furthermore, parental communication has been found to Unclear.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The results of their systematic review found that parental monitoring, parent-child interaction, and child disclosure led to delayed alcohol initiation as well as reduced levels of later drinking [68]. Additional support for the findings of the current systematic review were found in the results of other studies which show that parental monitoring significantly decreases adolescent risk behaviour such as sexual risk behaviours and decreased substance use [26,56,60,67]. Furthermore, parental communication has been found to Unclear.…”
Section: Discussionsupporting
confidence: 74%
“…The Open Family Studies Journal, 2015, Volume 7 21 ( have the same effect, especially for mother-son dyads and father-daughter dyads [28,56,69]. …”
Section: The Effects Of Parental Monitoring and Communicationmentioning
confidence: 99%
“…Generally, the greater the number of risk factors present, the greater the risk of developing more severe addiction. [87][88][89][90] Hence, the importance of investing in prevention programs and early diagnosis.…”
Section: Psychiatric Comorbiditiesmentioning
confidence: 99%
“…Further, the emergence of single parent families poses signifi cant questions on the bearing it has on the children involved. While literature in the western contexts exist, very few emphasize the individual role of the primary parent 43 and their parenting practices or on the infl uence that the extended family exerts in the emergence of these behaviours.…”
Section: The Demographics Of Problem Behaviourmentioning
confidence: 99%
“…Although the structure itself is devolving, this can be described as 'changing' as against 'breaking down.' The unique aspect is that the smaller nuclear units draw their functional and emotional support from the larger family system 42,43 . The increasing need for economic autonomy has been one of the primary reasons for this shift.…”
Section: The Demographics Of Problem Behaviourmentioning
confidence: 99%